Endothelium‐Independent Vasorelaxation Effects of Sigesbeckia glabrescens (Makino) Makino on Isolated Rat Thoracic Aorta. (30th October 2012) - Lee, Kyungjin; Jung, Jinho; Yang, Gabsik; Ham, Inhye; Bu, Youngmin; Kim, Hocheol; Choi, Ho‐Young
Abstract : The present study aimed to investigate the vasorelaxant effect of the methanol extract of Sigesbeckia glabrescens (Makino) Makino (MESG) on rat aortic rings and mechanism of action. MESG inhibited both noradrenaline bitartrate (NA)‐ and potassium chloride (KCl)‐induced contraction of endothelium‐intact aortic rings in a concentration‐dependent manner. Removal of the endothelium did not influence the effect of MESG on NA‐precontracted aortic rings. Pretreatment with MESG (250 µg/mL) inhibited calcium chloride‐induced vasocontraction of NA‐ or KCl‐precontracted endothelium‐denuded aortic rings. It also relaxed phorbol‐12‐myristate‐13‐acetate‐induced contraction of aortic rings in a concentration‐dependent manner. In addition, Bay K8644 (anL ‐type calcium channel opener) vasocontracted in MESG pretreated aortic rings. On the other hand, the inositol 1, 4, 5‐triphosphate receptor, the ryanodine receptor, the Rho‐kinase inhibitor (Y‐27632), a soluble guanylyl cyclase blocker (1‐H‐[1, 2, 4]‐oxadiazolo‐[4, 3a]‐quinoxalin‐1‐one), and K + channel blockers (glybenclamide, tetraethylammonium, and 4‐aminopyridine) did not affect the effect of MESG. These results suggested that the mechanism underlying the vasorelaxant effect of MESG is mediated by endothelium‐independent pathways. This specifically refers to blockade of the influx of extracellular Ca 2+ via receptor‐operative Ca 2+ channels and voltage‐dependent Ca 2+ channels and inhibition of a protein kinase C‐mediated cellular pathway. Copyright © 2012 John Wiley & Sons, Ltd.